Stroke and the BBB - Cipolla, Marilyn (Henry Stewart Talks, 2008)
Ischemic brain injury, Cytotoxic and vasogenic brain edema, Role of BBB in brain edema during stroke, Cellular regulation of BBB permeability, Reperfusion injury, Oxidative damage, Aquaporins and brain edema, Mediators of brain edema, Hemodynamic change during stroke
Archived at 2018/05/31